Soil carbon dynamics in the temperate Himalayas: Impact of land use management - Kumar, Shamal Shasang; Wani, Owais Ali; Mir, Shakeel Ahmad; Babu, Subhash; Sharma, Vikas; Chesti, Majeed Ul Hassan; Baba, Zahoor Ahmad; Sofi, Parvaze Ahmad; Wani, Fehim Jeelani; Dar, Shahnawaz Rasool; Singh, Raghavendra; Yadav, Devideen (Frontiers in Environmental Science, 2022)
Food security and environmental health are directly linked with soil carbon (C). Soil C plays a crucial role in securing food and livelihood security for the Himalayan population besides maintaining the ecological balance in the Indian Himalayas. However, soil C is being severely depleted due to anthropogenic activities. It is well known that land use management strongly impacted the soil organic carbon (SOC) dynamics and also regulates the atmospheric C chemistry. Different types of cultivation practices, i.e., forest, plantations, and crops in the Kashmir Himalayas, India, has different abilities to conserve SOC and emit C in the form of carbon dioxide (CO2). Hence, five prominent land use systems (LUC) (e.g., natural forest, natural grassland, maize-field-converted from the forest, plantation, and paddy crop) of Kashmir Himalaya were evaluated to conserve SOC, reduce C emissions, improve soil properties and develop understanding SOC pools and its fractions variations under different land use management practices. The results revealed that at 0-20 cm and 20-40 cm profile, the soil under natural forest conserved the highest total organic carbon (TOC, 24.24 g kg-1 and 18.76 g kg-1), Walkley-black carbon (WBC, 18.23 g kg-1 and 14.10 g kg-1), very-labile-carbon (VLC, 8.65 g kg-1, and 6.30 g kg-1), labile-carbon (LC, 3.58 g kg-1 and 3.14 g kg-1), less-labile-carbon (VLC, 2.59 g kg-1, and 2.00 g kg-1), non-labile-carbon (NLC, 3.41 g kg-1 and 2.66 g kg-1), TOC stock (45.88 Mg ha-1 and 41.16 Mg ha-1), WBC stock (34.50 Mg ha-1 and 30.94 Mg ha-1), active carbon pools (AC, 23.14 Mg ha-1 and 20.66 Mg ha-1), passive carbon pools (PC, 11.40 Mg ha-1 and 10.26 Mg ha-1) and carbon management index (CMI, 100), followed by the natural grassland. However, the lowest C storage was reported in paddy cropland. The soils under natural forest and natural grassland systems had a greater amount of VLC, LC, LLC, and NLC fraction than other land uses at both depths. On the other hand, maize-field-converted-from-forest-land-use soils had a higher proportion of NLC fraction than paddy soils; nonetheless, the NLC pool was maximum in natural forest soil.